PSYCHOPHYSIOLOGICAL BASIS OF EMPATHY - Gavrilov, V.V. (Modern Psychology, 2021)
The ability to empathize is one of the most important in relationships between individuals: it "forces" them to change their behavior, sometimes to their detriment, leads to group cohesion, etc., which makes the study of empathy important and relevant. There are different types of empathy, while only people are usually endowed with true empathy, and ideas about the organization of brain activity and the psychophysiological foundations of empathy are extremely few. Recently, the manifestations of empathy have been associated with the functioning of systems of "mirror neurons", and the phenomenon of empathy itself has been considered on two levels: innate, associated with the presence of" mirror systems", and acquired, associated with"cognitive processing of information". The uncertainty in the definition of empathy, the methodological difficulties and limitations of research on empathy in humans, on the one hand, and the ideas about the structure of individual experience and the organization of brain activity developed in the system- evolutionary approach [2, 3], on the other, allow us to assume that the psychophysiological basis of empathy can be understood as a result of the study of the organization of brain activity in the implementation of "empathic" behavior. The results of a study of empathy and the organization of brain activity in rats in a model of instrumental food-acquisition behavior are reported.